The Effect Of Psychological Support On Psychological Security, Marital Compatibility And Hardiness Of The Newly Married Women - Ahmedi, Khaoula; Mezaini, Djilali (جامعة الوادي - University of Eloued, 2023)
تهدف الدراسة الحالية إلى التحقق من أثر المرافقة النفسية في تحقيق الأمن النفسي والتوافق الزواجي والصلابة النفسية للمرأة حديثة الزواج، ولتحقيق هذا الهدف تم استخدام المنهج التجريبي تصميم مجموعة واحدة قياس قبلي وبعدي، وطبقت الدراسة على عينة قوامها (15) زوجة، وتم التوصل من خلال استخدام مقياس الأمن النفسي، ومقياس التوافق الزواجي، ومقياس الصلابة النفسية، وباستخدام الأساليب الإحصـائية المتمثلة فـي اختبار T للفروق بين متوسطين إلى ما يلي: 1. توجد فروق في درجات مقياس الأمن النفسي بين القياس القبلي والبعدي. 2. توجد فروق في درجات مقياس التوافق الزواجي بين القياس القبلي والبعدي. 3. توجد فروق في درجات مقياس الصلابة النفسية بين القياس القبلي والبعدي. واعتمادا على النتائج المتوصل إليها تبين الأثر الايجابي لاستخدام المرافقة النفسية، وذلك من خلال تأثيرها إيجابا بكل من الأمن النفسي، التوافق الزواجي، والصلابة النفسية، الأمر يبين ضرورة استخدام المرافقة النفسية من قبل المختصين للمساعدة في حل المشكلات المختلفة. Abstract: The present study aims to examine the effect of the psychological support on the psychological security, marital compatibility and hardinessness of newly married women. In orderto conduct this research, a repeated measures ( pre-post) design was used. The study sample consisted of (15) newly married wives.And to gather data,three different instruments were used (Psychological Security, the Marital Compatibility , and Hardiness scales).The study results revealed that there was significant mean differences in the study variables. Finally, results revealed that the participants rated themselves significantly higher on overall scales in the post-test compared to pre- test.
(an Experimental Study In Algiers)
مقال
Keywords: psychological support; psychological security ; marital compatibility . hardiness ; newly married women